Teledermatology in the diagnosis of melanoma. (January 2014) - Karavan, Mahsa; Compton, Nicholas; Knezevich, Stevan; Raugi, Gregory; Kodama, Samantha; Taylor, Leslie; Reiber, Gayle E
Summary: We conducted a retrospective chart review of US Veterans in the Pacific Northwest area to compute melanoma incidence and Breslow depth at diagnosis. We compared Veterans with access to teledermatology (TD) and those without (non-TD). We identified pathology-confirmed primary melanomas in Veterans who had had at least one encounter at a VA facility during a 3-year study period. The age-adjusted melanoma incidence for all, TD and non-TD Veterans was 36, 15 and 57 per 100, 000, respectively. The mean Breslow depth was significantly greater in the TD group ( P = 0.03). Although a higher proportion of thin (Breslow depth ≤1 mm) TD melanomas were mitotically active, this difference was not significant. We also found that 180 (40%) of the non-TD (face-to-face) diagnosed melanomas were from Veterans living in areas where TD was available. This suggests that the higher melanoma incidence in the non-TD group was mainly due to under-utilization of TD services. The study demonstrated that the TD service was not fully utilized in the VISN20 region, although the reasons for this are not clear. Where TD was utilized it tended to diagnose more advanced melanomas with worse initial prognosis.